2002
DOI: 10.1007/s10021-001-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Balance Analyses of Boreal Forest Population Cycles: Merging Demographic and Ecosystem Approaches

Abstract: Using Ecopath, a trophic mass-balance modeling framework, we developed six models of a Canadian boreal forest food web centered around snowshoe hares, which have conspicuous 10-year population cycles. Detailed models of four phases of the cycle were parameterized with long-term population data for 12 vertebrate taxa. We also developed five other models that, instead of observed data, used parameter values derived from standard assumptions. Specifically, in the basic model, production was assumed to equal adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…ECOPATH has been widely used in fisheries research, but there are almost no applications of this model to terrestrial ecosystems (Ruesink et al 2002). We have reached two tentative conclusions from our modeling of trophic flows at these arctic sites.…”
Section: 00mentioning
confidence: 62%
See 1 more Smart Citation
“…ECOPATH has been widely used in fisheries research, but there are almost no applications of this model to terrestrial ecosystems (Ruesink et al 2002). We have reached two tentative conclusions from our modeling of trophic flows at these arctic sites.…”
Section: 00mentioning
confidence: 62%
“…If lemming predators increase with a time lag, predator numbers after a lemming peak will not be in an equilibrium and their impact could be significantly higher than we have observed, which would further increase the EE value during the decline phase of the cycle. A similar scenario was modeled with data from cyclic snowshoe hare populations by Ruesink et al (2002).…”
Section: 00mentioning
confidence: 99%
“…We used a mass balance ecosystem modeling software, Ecopath with Ecosim (EwE), that has been used extensively to study marine and aquatic food webs (Christensen et al 2008) as well as terrestrial ones (Ruesink et al 2002, Krebs et al 2003. Ecopath with Ecosim combines software for ecosystem mass balance analysis (Ecopath) with a dynamic modeling capability (Ecosim) to forecast species abundance in exploited ecosystems.…”
Section: Mass Balance Modelingmentioning
confidence: 99%
“…The phase of the cycle was assigned based on lemming abundance obtained by trapping (see the Appendix) following Bêty et al (2002). Intermediate years typically occurred ''post-peak'' (Gruyer et al 2008), which differs from other cycles in which intermediate years often occur before peaks (i.e., increase phase; Ruesink et al 2002, Gilg et al 2003. Consumption Q and production P were assessed both empirically and allometrically, using primarily the equations of Banse and Mosher (1980) and Nagy (1987) in the latter case.…”
Section: Mass Balance Modelingmentioning
confidence: 99%
“…A recently completed long-term experiment in the Kluane region of the southwest Yukon Territory, Canada, demonstrated that predation is the proximal cause of the decline of the hare population in each cycle (Krebs et al 2001b). However, the factors (likely food and predation) that contribute to the 10-year timing of the cycle (Ruesink et al 2002), the exact causes of the sustained low phase after the crash (Boonstra et al 1998;Hodges et al 1999), and the phenomena that synchronize the cycle across the boreal forest region of North America (Sinclair and Gosline 1997) have yet to be conclusively determined. It is clear that the hare cycle itself is an important driver of biotic interactions in the boreal forest (Krebs et al 2001b).…”
Section: Introductionmentioning
confidence: 99%